2018
DOI: 10.1007/s00213-018-4965-x
|View full text |Cite
|
Sign up to set email alerts
|

Oprm1 A112G, a single nucleotide polymorphism, alters expression of stress-responsive genes in multiple brain regions in male and female mice

Abstract: BackgroundOPRM1 A118G, a functional human mu-opioid receptor (MOR) polymorphism, is associated with drug dependence and altered stress responsivity in humans as well as altered MOR signaling. MOR signaling can regulate many cellular processes, including gene expression, and many of the long-term, stable effects of drugs and stress may stem from changes in gene expression in diverse brain regions. A mouse model bearing an equivalent polymorphism (Oprm1 A112G) was previously generated and studied. Mice homozygou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Previous work from our lab demonstrate that both male and female GG animals exhibit decreased MOR mRNA expression and protein levels compared to AA animals, and this is associated with reduced locomotor response to opioids 6,8. A recent study investigating baseline mRNA expression levels of drug-and stress-related genes in A112G mice found that hypothalamic expression of the neuropeptides arginine vasopressin (Avp) and galanin (Gal), and hippocampal expression of the opioid-related nociception receptor (Oprl1) and cannabinoid receptor 1 (Cnr1) were significantly reduced in animals with the G allele (Collins 2018). Thus, the influence of the Oprm1 SNP in these studies may be due to differential expression of opioid receptors and/or an attenuation of MOR-mediated transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work from our lab demonstrate that both male and female GG animals exhibit decreased MOR mRNA expression and protein levels compared to AA animals, and this is associated with reduced locomotor response to opioids 6,8. A recent study investigating baseline mRNA expression levels of drug-and stress-related genes in A112G mice found that hypothalamic expression of the neuropeptides arginine vasopressin (Avp) and galanin (Gal), and hippocampal expression of the opioid-related nociception receptor (Oprl1) and cannabinoid receptor 1 (Cnr1) were significantly reduced in animals with the G allele (Collins 2018). Thus, the influence of the Oprm1 SNP in these studies may be due to differential expression of opioid receptors and/or an attenuation of MOR-mediated transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in a longitudinal 4-year familial study of mothers ( n = 2,460) and children ( n = 3,720), there was no association of the G allele with body mass index (BMI) or waist circumference (Hardman et al., 2014). It has been demonstrated, however, that GG mice show a reduction in hypothalamic gene expression AVP (arginine vasopressin) and Gal (galanin) (Collins et al., 2018). Additionally, it is possible, as our results suggest, that mice with the A112G variant have impairments in body weight compensation following repeated bouts of intermittent calorie deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…We have further characterized the heterozygous mice, 112AA versus 112GG, investigating differences in baseline (opioid-naive) gene expression of several genes that interact with the endogenous opioid system in diverse brain regions of adult mice (Collins et al 2018). We found several gene expression alterations, most strongly the expression levels of the precursors of the neuropeptides arginine vasopressin and galanin in the hypothalamus and the expression of opioid receptor-like receptor (ORL1; target of orphanin FQ/nociceptin peptide) and cannabinoid receptor type 1 (CB 1 ) in the hippocampus.…”
Section: Mouse Models Of Particular Genetic Variantsmentioning
confidence: 99%